Cytokine-mediated modulation of the hepatic miRNome: miR-146b-5p is an IL-6-inducible miRNA with multiple targets. Issue 5 (26th August 2018) - Kirchmeyer, Mélanie; Servais, Florence A; Hamdorf, Matthias; Nazarov, Petr V; Ginolhac, Aurélien; Halder, Rashi; Vallar, Laurent; Glanemann, Matthias; Rubie, Claudia; Lammert, Frank; Kreis, Stephanie; Behrmann, Iris
Abstract: Interleukin-6 (IL-6)-type cytokines play important roles in liver (patho-)biology. For instance, they regulate the acute phase response to inflammatory signals and are involved in hepatocarcinogenesis. Much is known about the regulation of protein-coding genes by cytokines whereas their effects on the miRNome is less well understood. We performed a microarray screen to identify microRNAs (miRNAs) in human hepatocytes which are modulated by IL-6-type cytokines. Using samples of 2 donors, 27 and 68 miRNAs (out of 1, 733) were found to be differentially expressed upon stimulation with hyper-IL-6 (HIL-6) for up to 72 h, with an overlap of 15 commonly regulated miRNAs. qPCR validation revealed that miR-146b-5p was also consistently up-regulated in hepatocytes derived from 2 other donors. Interestingly, miR-146b-5p (but not miR-146a-5p) was induced by IL-6-type cytokines (HIL-6 and OSM) in non-transformed liver-derived PH5CH8 and THLE2 cells and in Huh-7 hepatoma cells, but not in HepG2 or Hep3B hepatoma cells. We did not find evidence for a differential regulation of miR-146b-5p expression by promoter methylation, also when analyzing the TCGA data set on liver cancer samples. Inducible overexpression of miR-146b-5p in PH5CH8 cells followed by RNA-Seq analysis revealed effects on multiple mRNAs, including those encoding IRAK1 and TRAF6 crucial for Toll-like receptor signaling. Indeed, LPS-mediated signaling was attenuated upon overexpression of miR-146b-5p, suggesting a regulatory loop to modulate inflammatory signaling in hepatocytes. Further validation experiments suggest DNAJC6, MAGEE1, MPHOSPH6, PPP2R1B, SLC10A3, SNRNP27, and TIMM17B to be novel targets for miR-146b-5p (and miR-146a-5p). IL-6-type cytokines up-regulate miR-146b-5p expression in liver cells, an anti-inflammatory miRNA with multiple targets shared with miR-146a-5p.